2020
DOI: 10.3389/fevo.2020.00123
|View full text |Cite
|
Sign up to set email alerts
|

Extensive Overlap in the Selection of Wild Fruits by Chimpanzees and Humans: Implications for the Management of Complex Social-Ecological Systems

Abstract: Understanding the capacity for humans to share resources (crops, wild foods, space) with large-bodied wildlife is vital for biodiversity conservation and human wellbeing, and requires comprehensive examination of their temporal interactions over fine spatial scales. We combined ecological (plant identification, wild fruit availability plots, animal fecal and trace sampling) and social science (free-listing, semi-structured interviews, participant observation) methods to systematically and simultaneously collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 52 publications
0
22
0
Order By: Relevance
“…It is estimated that there are 10-12 chimpanzee communities in CNP as a whole (Bersacola, 2019). In the forested areas of centralsouthern CNP, genetic, behavioural and ecological research support the presence of seven different chimpanzee communities (Hockings and Sousa, 2013;Sá, 2013;Bessa et al, 2015;Bersacola, 2019;Vieira et al, 2019;Hockings et al, 2020); these include the four studied communities: Caiquene-Cadique, Lautchandé, Madina and Cambeque. Due to the unhabituated nature of these communities, at present little is known about their community sizes and compositions; nonetheless, previous works estimate that the communities' range between 35-60 individuals (Bessa et al, 2015;Vieira et al, 2019).…”
Section: Study Sitementioning
confidence: 91%
See 1 more Smart Citation
“…It is estimated that there are 10-12 chimpanzee communities in CNP as a whole (Bersacola, 2019). In the forested areas of centralsouthern CNP, genetic, behavioural and ecological research support the presence of seven different chimpanzee communities (Hockings and Sousa, 2013;Sá, 2013;Bessa et al, 2015;Bersacola, 2019;Vieira et al, 2019;Hockings et al, 2020); these include the four studied communities: Caiquene-Cadique, Lautchandé, Madina and Cambeque. Due to the unhabituated nature of these communities, at present little is known about their community sizes and compositions; nonetheless, previous works estimate that the communities' range between 35-60 individuals (Bessa et al, 2015;Vieira et al, 2019).…”
Section: Study Sitementioning
confidence: 91%
“…Specifically, no long-term studies have yet reached the westernmost populations of the species' distribution. Recent work in Cantanhez National Park (CNP), Guinea-Bissau, has started to fill this gap (Sousa et al, 2011;Hockings and Sousa, 2012;Bessa et al, 2015;Vieira et al, 2019;Hockings et al, 2020). For example, a 9-month study at CNP found, through the analysis of faecal samples and other indirect data, that these chimpanzees fed on wild bee honey with some degree of frequency, however no tools were ever found (Bessa et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…At Cantanhez NP, humans and chimpanzees show substantial overlap in their use of space, and encounter each other regularly on roads, paths and around the edges of villages and agricultural areas. Humans and chimpanzees use at least 27 of the same wild fruit species, including oil palm (Elaeis guineensis), velvet tamarind (Dialium guineensis), and saba (Saba senegalensis) (Hockings et al, 2020), with chimpanzee use of space driven partly by the availability of oil-palm fruit (Bersacola et al, 2021). Although the Caiquene-Cadique community of chimpanzees in central Cantanhez NP use areas away from villages and agriculture more intensively, they optimise their foraging strategies when wild fruits are scarce by increasing their use of village areas with cultivated fruits (Bersacola et al, 2021).…”
Section: The Environment Biodiversity and Human-wildlife Resource Overlapmentioning
confidence: 99%
“…Humans and primates share space across many different habitats spanning the primate distribution range, including forests, open woodlands, agricultural landscapes, roadsides, villages, and urban landscapes (Estrada et al, 2017;Hockings et al, 2015;Radhakrishna, Huffman, & Sinha, 2013). Because humans and primates have broadly similar physiological needs and diets, these sympatric contexts can lead to ecological competition in forests and agricultural landscapes (Hockings, Parathian, Bessa, & Frazão-Moreira, 2020;Riley, 2007), as well as create opportunities for provisioning and other close encounters between species.…”
Section: Risk Of Zoonosis At the Human-primate Interfacementioning
confidence: 99%